Linking cognitive functioning and postural balance control through virtual reality environmental manipulations - Imaoka, Yu; Hauri, Laura; Flury, Andri; de Bruin, Eling D. (Frontiers in Aging Neuroscience, 2022)
Background: Dementia is becoming a relevant problem worldwide. A simple screening at an early stage will be important to detect the risk of developing dementia. Vestibular dysfunction is likely to be associated with cognitive impairment. Since head-mounted display (HMD) virtual reality (VR) technology has the potential to activate the vestibular function, assessing postural sway with visual stimulation using HMD VR technology could be potentially useful for dementia screening. Objective: The purpose of this study is to evaluate the effect of HMD-based VR visual stimuli on posture in older adults and the relationship between the stimulated body sway behaviours and cognitive performance. Method: Using a cross-sectional study design, we investigated the effect of optokinetic design-based room with stripes (OKR) VR environment oscillating forwards and backwards at 23/60Hz. Centre of pressure (COP) displacement was measured in older adults aged 65 years and over in the OKR VR environment. Frequency response of COP was compared to cognitive performance of Montreal Cognitive Assessment (MoCA). Results: 20 healthy older adults (70.4 ± 4.9 years; 27.2 ± 1.6 MoCA score) and 3 people with mild cognitive impairment (74.7 ± 4.0 years; 20.3 ± 2.1 MoCA score) were assessed. The results reveal that the oscillating OKR VR environment induced different postural sway in anterior-posterior direction in the real world. Correlation analysis shows that the cognitive test score was associated with the frequency response of stimulated postural sway in anterior-posterior direction (frequency Band 1 of 0 − 0.5Hz related to the visual and vestibular systems: rs = 0.45, P = 0.03). Conclusion: Outcomes would suggest that a potential link may emerge between cognition and posture when the HMD-based VR visual stimuli are applied. The simple screening of stimulated postural sway could explain cognitive functioning. Further studies are warranted to clarify the vestibular system and spatial cognitive function more specifically in the proposed assessment system.